Value Perception and Streaming Intentions: Exploring Social Identity Mediation in Indonesian OTT Users - Shaomi Fujiyanti Amalia; Nurafni Rubiyanti; Arry Widodo; Anita Silvianita (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the era of digital technology development and the influence of the pandemic, there has been a shift in media consumption patterns among society which has successfully driven the rise of Over-The-Top (OTT) platform streaming services. This phenomenon has opened up huge opportunities for digital marketers who are looking for unique ways to approach their consumers. This research aims to validate the Perceived Value Theory and Social Identity Theory models in predicting people's attitudes towards Future Behavioral Intention. The sampling technique in this research used nonprobability sampling. The sampling method used was purposive sampling. The sample in this research is consumers who have used Over-The-Top (OTT) streaming services in Indonesia. The analysis technique used is Partial Least Squares (PLS) with Structural Equation Modeling (SEM). SEM-PLS is a statistical analysis method used to validate structural equation models that include latent variables.